Prognosis of immune checkpoint inhibitor-induced myasthenia gravis: a single center experience and systematic review - Qin, Yuhui; Chen, Siyuan; Gui, Qian; Zhang, Teng; Li, Yanan; Du, Zhijuan; Lv, Yahui; Du, Xiangyu; Hu, Yi; Liu, Zhefeng (Frontiers in Neurology, 2024)
Background Immune checkpoint inhibitors (ICI)-induced myasthenia gravis (MG) is an uncommon but potentially fatal neurotoxicity. We aim to help physicians familiarize themselves with the clinical characteristics of ICI-induced MG, facilitating early diagnosis and prompt intervention. Methods We searched the Chinese People’s Liberation Army General Hospital medical record system from January 2017 to August 2023 for patients diagnosed with ICI-induced MG. We systematically reviewed the literature until August 2023 to identify all similar patients. We collected clinical information on these patients. Results 110 patients were identified, 9 from our institution and 101 from case reports. In our institution, Median age was 66 years (range: 49–79 years). 6 were males. The most common was lung cancer (n = 4). All patients had no previous history of MG and received PD-1 or PD-L1 inhibitors. The median time from ICI initiation to first MG symptoms was 4 weeks (range: 2–15 weeks). ICIs were discontinued in all patients. Most patients initially received high-dose corticosteroids, and their symptoms improved. Some patients are discharged with corticosteroids maintenance therapy. In addition, 55 patients (50%) with concomitant myositis and/or myocarditis and MG-induced mortality were more common in the myositis and/or myocarditis group (10.9% vs. 34.5%, p = 0.016). Overlap of myositis with MG (OR = 3.148, p = 0.009) and anti-AChR antibody positivity (OR = 3.364, p = 0.005) were both significantly associated with poor outcomes. Conclusion Our study reveals the prognosis of ICI-induced MG and suggests that myositis and/or myocarditis are severe comorbidities of ICI-induced MG, emphasizing the importance of early diagnosis and clinical intervention.